Simulacra and fakes in the information warfare - Марина Колінько; Галина Петришин (Cхід)
The article is devoted to the study of political communication, inscribed into the new sociocultural and political systems of relations, into the wartime conditions. It has been proven that information media and network communications not only influence the behavior of social subjects, but can also destroy ideas about order, justice, and morality if they are exposed to the propaganda technologies of an aggressive state. In the structure of information influence, propaganda plays a decisive role, its task is to spread ideas and views, true or half-true facts, outright lies or rumors with the aim of manipulating public consciousness. The special relevance of this problem in the context of information support of the actions of the Russian authorities during Russia’s war against Ukraine is emphasized.